Field accuracy of fourth-generation rapid diagnostic tests for acute HIV-1: a systematic review. (28th November 2015) - Lewis, Joseph M.; Macpherson, Peter; Adams, Emily R.; Ochodo, Eleanor; Sands, Anita; Taegtmeyer, Miriam
Abstract : Introduction: Fourth-generation HIV-1 rapid diagnostic tests (RDTs) detect HIV-1 p24 antigen to screen for acute HIV-1. However, diagnostic accuracy during clinical use may be suboptimal. Methods: Clinical sensitivity and specificity of fourth-generation RDTs for acute HIV-1 were collated from field evaluation studies in adults identified by a systematic literature search. Results: Four studies with 17 381 participants from Australia, Swaziland, the United Kingdom and Malawi were identified. All reported 0% sensitivity of the HIV-1 p24 component for acute HIV-1 diagnosis; 26 acute infections were missed. Specificity ranged from 98.3 to 99.9%. Conclusion: Fourth-generation RDTs are currently unsuitable for the detection of acute HIV-1. Abstract : Supplemental Digital Content is available in the text